The Marketing strategies of the sugar cane production units of the Valle del Turbio, Peña Municipality, Yaracuy state, Venezuela (Revista Científica Compendium, 2020)
The general objective of this research was to describe the marketing strategies applied by the Sugar Cane Production Units, Valle del Turbio, Peña, Municipality, Yaracuy state, Venezuela (Period 2016-2017). A total of 7 producers were selected as part of the sample. They are part of the SAGAZ system of the company Azucarera Río Turbio, C.A. It is a descriptive field study, with a non-experimental, transactional design. Two instruments were developed in order to evaluate the business environment (survey) and the marketing mix (interview script). The main results include an evaluation matrix of external factors, the characterization of the production units studied and the main strategies applied. One of the main conclusions establishes that the business environment is perceived as one of high uncertainty, opportunities are not fully exploited, threats require taking actions for survival in order to adapt to periods of crisis.
Keywords: management; marketing; strategies; sugar cane production units